(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the characteristics of local injuries in patients bitten by cobras (Naja spp) treated at Bach Mai Hospital from July 2023 to June 2024. Methods: A cross-sectional descriptive study on 117 patients bitten by cobras. Results: The majority of cases involved N. atra bites, accounting for 70.9%, with 82.1% of bites occurring on the hands. Bites with a single fang mark accounted for half of the patients (50.4%). Clinical manifestations at the site showed pain in 94.9% of patients, with an average pain score of 6.2±2.3, median 7. Swelling was observed in 80.3% of patients, with an average limb circumference difference of 1.6±1.9 cm, median 1 cm. Spread of venom was noted in 82.9% of patients, with an average spread area of 15.9±11.7 cm², median 12 cm². Necrosis was present in 58.1% of patients, with an average necrotic area of 10.2±16.9 cm², median 4 cm². Conclusion: There are various forms of local injuries caused by cobra bites, such as pain, swelling, spread of venom, and necrosis.